Improving Early Childhood Education Management through Problem Identification of Institutions - Upik Elok Endang Rasmani; Warananinngtyas Palupi; Jumiatmoko Jumiatmoko; Nurul Shofiatin Zuhro; Anjar Fitrianingtyas (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
The success of managing early childhood education institutions is determined by management aspects such as curriculum, infrastructure, marketing, students, supervision and educators. One of the most important management is management that regulates education personnel because this management determines how educators provide facilities to develop children's abilities so that they can achieve the expected educational goals. This study aims to improve PAUD (Early Childhood Education) Management by identifying institutional problems. This study used a qualitative descriptive research model. The research sample was teachers in Kindergarten AULIA Surakarta. The results showed that the observation, attention, communication, personality of the teacher and the child was good and the teacher always conducted consultations on children's problems. It showed that the average AULIA Surakarta kindergarten teacher had done their job well.